Women Latin poets language, gender, and authority, from antiquity to the eighteenth century - Stevenson, Jane (Oxford University Press, 2005)
Women Latin Poets addresses women's relationship to culture between the first century B.C. and the eighteenth century A.D. by studying women's poetry in Latin. Based entirely on original archival research in twelve countries, Stevenson recovers an aspect of history often deemed not to exist: women who achieved public recognition in their own time, sometimes to a startling extent. Presenting, often for the first time, the work of more than three hundred women Latin poets, all translated and included in a comprehensive finding guide, Women Latin Poets substantially revises received opinion on women's participation in, and relation to, ?lite culture. The sheer number of female Latin poets will require women's historians to completely re-evaluate the idea that all women had "no access to education" before the nineteenth century.